An exploratory study of the knowledge, attitudes and perceptions of advance care planning in family caregivers of patients with advanced illness in Singapore. Issue 3 (4th September 2012) - Ng, Raymond; Chan, Susan; Ng, Tzer Wee; Chiam, Ai Ling; Lim, Sthenos
Abstract : Objective: The aim of this study was to examine the knowledge, attitudes and perceptions of advance care planning (ACP) in caregivers of patients with advanced illness in Singapore. Methods: Family caregivers of patients within the palliative care unit in a hospital and a hospice were purposively recruited and interviewed. Qualitative content analysis was carried out exploring key themes and subthemes emerging from the data. Results: Between May 2009 and May 2010, 18 participants were interviewed. All participants interviewed had low awareness of ACP and the Advance Medical Directive but felt that ACP is important. Perceived benefits of ACP were that it respects autonomy, guides patients and families, and reduces burden of decision-making near the end-of-life. Barriers to ACP include non-disclosure of diagnosis as well as uncertainty of when and how ACP should be broached. There was a reticence to talk openly about issues surrounding end-of-life care as a result of cultural taboo and a fear that doing so will destroy hope. While all participants would consider ACP for themselves, some were ambivalent about discussing ACP for their loved ones, especially when their loved ones were of an older generation. Involvement of the family unit and physicians in ACP were viewed as important. Conclusion: This study highlights the need for public education on the benefits and process of ACP in Singapore. In formulating an approach to ACP, there is a need to take into account cultural sensitivities towards ACP discussions and the importance of closely involving the family unit in the process.